2015
DOI: 10.1016/j.celrep.2014.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of 17q21.31/WNT3-WNT9B Amplification in hPSCs with Respect to Neural Differentiation

Abstract: SUMMARY Human pluripotent stem cell (hPSC) lines exhibit repeated patterns of genetic variation, which can alter in vitro properties as well as suitability for clinical use. We examined associations between copy number variations (CNVs) on chromosome 17 and hPSC mesodiencephalic dopaminergic (mDA) differentiation. Among 24 hPSC lines, two karyotypically-normal lines, BG03 and CT3, and BG01V2, with trisomy 17, exhibited amplification of the WNT3/WNT9B region and rapid mDA differentiation. In hPSC lines with amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…This could be partially More recently, mES cell differentiation was found to be accompanied by activation of noncanonical signaling via increased expression of Tcf3 [171], which is known to signal independently of -catenin in several contexts [172]. This is consistent with our findings in human NSCs, where Wnt-3a promotes differentiation via JNK/ATF2 independently of β-catenin [163], and with a recent study in human iPS cells, which showed that Wnt-3 and Wnt-9B cooperate to promote dopaminergic differentiation, with canonical signaling maintaining proliferation and noncanonical signaling, involving JNK, driving differentiation [173]. These studies indicate that noncanonical signaling can play an important role during the differentiation of hES cells and warrant further studies of noncanonical Wnt [174].…”
Section: Human Neural Stem and Progenitor Cells: Intracellular Componsupporting
confidence: 92%
“…This could be partially More recently, mES cell differentiation was found to be accompanied by activation of noncanonical signaling via increased expression of Tcf3 [171], which is known to signal independently of -catenin in several contexts [172]. This is consistent with our findings in human NSCs, where Wnt-3a promotes differentiation via JNK/ATF2 independently of β-catenin [163], and with a recent study in human iPS cells, which showed that Wnt-3 and Wnt-9B cooperate to promote dopaminergic differentiation, with canonical signaling maintaining proliferation and noncanonical signaling, involving JNK, driving differentiation [173]. These studies indicate that noncanonical signaling can play an important role during the differentiation of hES cells and warrant further studies of noncanonical Wnt [174].…”
Section: Human Neural Stem and Progenitor Cells: Intracellular Componsupporting
confidence: 92%
“…A crucial benchmark for clinically relevant mDA neurons is TH expression. The majority in vitro differentiation studies report 15–30% TH positive cells after 25–45 days of differentiation on 2D platforms164041, and in 2D we similarly find 20% TH+ cells at D25. In contrast, in the 3D hydrogel we generated a higher quality, purer mDA neuronal population, with almost double the percentage of TH+ cells (37%) compared to our 2D control.…”
Section: Discussionsupporting
confidence: 67%
“…At a minimum, approximately 100,000 mDA neurons would need to engraft and survive within the striatum for effective disease treatment5. With purities of ~15–30% hPSC-derived mDA neurons167, and only 1–5% of implanted cells surviving as TH+ neurons post-implantation in pre-clinical models123, generating sufficient numbers of cells to treat the estimated 1 million PD patients in the US alone would be challenging. Even producing the ~10 9 cells typically needed for an in vitro pharmacology, toxicology, or genetic screen is daunting89.…”
mentioning
confidence: 99%
“…In recent years, genomic studies of individuals with developmental or neurodegenerative diseases have tremendously advanced our understanding of the genetics of these disorders [ 1 5 ]. Many of them, including autism spectrum disorder (ASD), schizophrenia, Alzheimer’s disease (AD), and Parkinson’s disease (PD), are caused by a heterogeneous combination of variant alleles and have therefore proven difficult to recapitulate in animal models, which are better suited for studying single-gene mutations [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%